BROADCAST MANAGEMENT OF LINTAS TAHUNA PAGI PROGRAM ON PRO 1 RRI YEAR IN ENCOURAGING PUBLIC PARTICIPATION - Dainga, Rigim Boy; Gilang Gusti AJi (The Commercium, 2025)
The thesis aims to analyze how management of broadcast programs broadcasted by morning contributes to encouraging public participation. The study used descriptive qualitative methods with a case study approach focusing on pro 1 rri tahuna as a broadcasting society. Data collection methods include interviews with broadcast managers and staff, observation, and document analysis for broadcast programs. Studies show that distribution management has not been done well and at best to encourage public participation in the early morning traffic program, and yet pro 1 rri tahuna has been seeking to encourage public participation in the annual traffic program by opening upa live stream on social media facebook, presenting a range of discussion topics that are relevant to the needs and interests of the listeners, And involve the public in planning and evaluating broadcast programs.